Peningkatan Pengetahuan Tentang Spiritualitas di Tempat Kerja dan Etika Kerja pada Sekolah Klasikal Terang Nusantara (SETARA) - Tongam Sirait; Regi Sanjaya (Jurnal Dharma Bhakti Ekuitas, 2026)
In Christian education, teachers and staff serve not only as educators but also as ministers and role models of faith. To respond to the challenges of the times, it is essential for them to continually strengthen spirituality in the workplace and uphold Christian work ethics. Spirituality provides the foundation for service, while work ethics reflect the values of faith. Therefore, Christian educators are called to embody love, faith, and exemplary character in their daily lives, so that teaching and learning become a means of shaping both character and faith in students. Alongside spirituality, work ethics play a vital role in cultivating a healthy Christian school culture. Values such as honesty, responsibility, discipline, and cooperation are expressions of faith manifested in daily actions. Integrity in the field of education not only enhances institutional quality but also provides students with tangible examples for developing holistic character. In this regard, Christian schools particularly Sekolah Klasikal Terang Nusantara (SETARA) must integrate faith into their practices to build education that is relevant, transformative, and rooted in Christ. The implementation of spirituality and work ethics requires renewal to remain responsive to contemporary challenges. Therefore, this Community Service Program (PKM) aims to revitalize understanding of spirituality and work ethics within the academic community of SETARA. Based on the post-PKM evaluation with the school (four months after the program), it was found that the knowledge and performance of the teachers and staff increased by 60% compared to before. Keywords : christian school, work ethics, workplace spirituality. Abstrak Dalam pendidikan Kristen, guru dan staf adalah pendidik sekaligus pelayan dan teladan iman. Untuk menjawab tantangan zaman, penting bagi mereka untuk terus memperkuat spiritualitas di lingkungan pekerjaan dan menjunjung tinggi etika kerja Kristiani. Spiritualitas menjadi dasar dalam melayani dan etika kerja mencerminkan nilai iman. Oleh sebab itu, pendidik Kristen dipanggil untuk menghadirkan kasih, iman, dan keteladanan dalam keseharian, sehingga pembelajaran menjadi sarana pembentukan karakter dan iman siswa. Selain spiritualitas, etika kerja berperan penting dalam membangun budaya sekolah Kristen yang sehat. Nilai-nilai kejujuran, tanggung jawab, disiplin, dan kerja sama menjadi cerminan iman yang diwujudkan dalam tindakan sehari-hari. Integritas dalam dunia pendidikan bukan hanya meningkatkan kualitas institusi, tetapi juga memberi teladan nyata bagi siswa dalam membangun karakter holistik. Sekolah Kristen dalam hal ini Sekolah Klasikal Terang Nusantara (SETARA) perlu mengintegrasikan iman demi membangun pendidikan yang relevan, transformatif, dan berakar pada Kristus. Implementasi spiritualitas dan etika kerja perlu diperbarui agar tetap relevan dengan tantangan kontemporer. Oleh karena itu, program Pengabdian kepada Masyarakat (PKM) ini bertujuan memberikan penyegaran wawasan terkait spiritualitas dan etika kerja di lingkungan civitas akademika SETARA. Dari hasil evaluasi pasca PKM dengan pihak sekolah (setelah 4 bulan dari PKM), didapati bahwa pengetahuan dan kinerja para guru dan staf meningkat 60% dibanding sebelumnya. Kata kunci: sekolah kristen, etika kerja, spiritualitas di tempat kerja.